BENDING MOMENT INFLUENCE SURFACES FOR RECTANGULAR CONCRETE PLATES SIMPLY SUPPORTED AT THREE EDGES AND BUILT-IN AT THE FOURTH EDGE (Journal of Engineering, 2010)
Presented in this paper is a series of bending moment influence surfaces for concrete rectangular plates simply supported at three edges and built-in at the fourth edge. The solutions are obtained analytically on the basis of thin plate's theory with small deflection using double Fourier series. The influence surfaces are presented for two observation points namely the center of the plate as well as the midpoint of the built-in edge. A computer program was written in FORTRAN language to generate the influence surfaces making use of the developed analytical solutions of this work. The validity of the computer solution was confirmed by comparing its results with published results for zero Poisson's ratio and excellent agreement was obtained. An application of the influence surfaces for the case of a line load as well as a strip load is also presented.The paper reveals that the bending moment influence surfaces depend on the actual value of Poisson's ratio, aspect ratio of the plate, and position of the observation point.